Kitab Henokh (4QEN) Di Qumran: Penemuan, Analisis Paleografi, Dan Signifikansinya Bagi Studi Era Bait Kedua - Daud, Daud; Bonggili, Martinus (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This study examines the Aramaic fragments of the Book of Enoch (4QEn; 4Q201–4Q212) from Qumran Cave 4 and their significance for Second Temple Judaism. It argues that 4QEn functioned not merely as apocalyptic literature but as a foundational theological framework shaping the Qumran community. Using an interdisciplinary qualitative approach—combining philological, paleographic, and comparative analysis—this study evaluates the role of Enochic traditions alongside texts such as Jubilees, Temple Scroll, and Community Rule. The findings indicate that 4QEn presents an integrated system encompassing cosmology, a 364-day calendrical structure, apocalyptic historiography, and ethical instruction. This study concludes that 4QEn played a central role in shaping Qumran’s theological identity and should be understood as part of the broader conceptual background of early Christian eschatology, without implying direct textual dependence.